Biodeterioration of stored castor (Ricinus communis) seeds by Aspergillus tamarii - ANTHONY NEGEDU; AMEH B. JOSEPH; VERONICA J. UMOH; SUNDAY E. ATAWODI; MAHENDRA RAI (Smujo International, 2014)
Abstract. Negedu A, Joseph Ab, Umoh VJ, Atawodi SE, Rai MK. 2014. Biodeterioration of stored castor (Ricinus communis) seeds by Aspergillus tamarii. Nusantara Bioscience 6: 126-131. Biodeterioration changes induced by Aspergillus tamarii in seeds of castor stored for a period of 180 days were investigated. Using Sabouroud Dextrose Agar (SDA) and direct plating methods, mycoflora associated with stored castor seeds were examined. The lipolytic ability of the isolates was determined based on free fatty acid production (quantitative). The effect of Aspergillus tamarii on moisture, total fat, crude protein, nitrogen-free extract, ash contents as well as free fatty acid and peroxide values were monitored bimonthly for six months during storage in the laboratory. In storage, Aspergillus tamarii caused significant (P ? 0.05) increases in free fatty acids, peroxide value, moisture content, crude protein, ash, and crude fiber contents and significantly (P ? 0.05) reduced the total fat and soluble sugar content (NFE) of the inoculated seeds compared to the uninoculated control. Aspergillus tamarii associated with stored castor seeds caused deteriorative changes in the seeds during storage period.